2020
DOI: 10.3390/microorganisms8030332
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effectiveness of Fecal Water and In Vitro Activity of a Multi-Strain Probiotic Formulation against Multi-Drug Resistant Microorganisms

Abstract: Introduction: Intestinal colonization with multi-drug resistant (MDR) microorganisms is a consequence of antimicrobial-induced gut dysbiosis. Given the effect of probiotics in modulating gut microbiota, the aim of the study was to investigate whether the ingestion of high concentration multi-strain probiotic formulation would change the antibacterial activity of the feces against clinical strains of MDR microorganisms. The corresponding in vitro antibacterial activity was also investigated. Materials/Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…The SBA was reported as a serum bactericidal titer and as a serial dilution number (SDN), which, in accordance with previous reports [ 33 ], corresponded to the number of the serial two-fold serum dilutions needed to obtain the corresponding serum bactericidal titer.…”
Section: Methodssupporting
confidence: 84%
“…The SBA was reported as a serum bactericidal titer and as a serial dilution number (SDN), which, in accordance with previous reports [ 33 ], corresponded to the number of the serial two-fold serum dilutions needed to obtain the corresponding serum bactericidal titer.…”
Section: Methodssupporting
confidence: 84%
“…In the case of FW genotoxicity, there are studies that show the protective effect of probiotics such as Bifidobacterium and Lactobacillus strains, among others [31]. In relation to other FW biomarkers, recently, Oliva et al [32] demonstrated that a 7-day probiotic supplementation also increased the faecal activity against multi-drug-resistant microorganisms in a pilot study that included healthy individuals (n = 6).…”
Section: Control Group (N = 3)mentioning
confidence: 99%
“…(2018) доказали, что он является потенциальным эффективным противомикробным препаратом в отдельности или в сочетании с известными лекарственными средствами против S. аureus. Включение экстракта в состав гидрогеля Burnshield усилило антисептический эффект и расширило спектр применения данного гидрогеля [8].…”
Section: актуальностьunclassified